Global patterns in island colonization during the Holocene - Leppard, TP; Cochrane, EE; Gaffney, D; Hofman, CL; Laffoon, JE; Bunbury, MME; Broodbank, C (Springer, 2022)
Analysis of the spatial and temporal structure of global island colonization allows us to frame the extent of insular human cultural diversity, model the impact of common environmental factors cross-culturally, and understand the contribution of island maritime societies to big historical processes. No such analysis has, however, been undertaken since the 1980s. In this paper we review and update global patterns in island colonization, synthesizing data from all the major island groups and theaters and undertaking quantitative and qualitative analysis of these data. We demonstrate the continued relevance of certain biogeographic and environmental factors in structuring how humans colonized islands during the Holocene. Our analysis also suggests the importance of other factors, some previously anticipated—such as culturally ingrained seafaring traditions and technological enhancement of dispersal capacity—but some not, such as the relationship between demographic growth and connectivity, differing trophic limitations impinging on colonizing farmers versus hunter-gatherer-foragers, and the constraining effects of latitude. We also connect colonization with continental dynamics: both the horizontal transmission of farming lifestyles earlier in the Holocene, and subsequent centrifugal processes associated with early state formation later in the Holocene.